Phase II clinical study of an association for the treatment of interstitial cystitis (Cystex®) - Souza, Gustavo H.B.; Maistro, Edson L. [UNESP]; Rodrigues, Marcelo; Carvalho, Jose C.T.; Fonseca, Fernando L.A.; Lopes, Andrey P.; Perazzo, Fabio F. (My University, 2012)
Painful bladder syndrome associated with interstitial cystitis (PBS/IC) is a clinical condition characterized pelvic pain, urinary urgency, and urinary frequency. In this study, 22 patients were assigned to make two visits over a three weeks period. The patients were randomly, double-blinded assigned in two groups. The first group received Cystex® capsules. The second group received placebo capsules. Two capsules were taken three times a day away from meals. The change from baseline in the O'Leary-Sant IC symptom and problem index was the primary outcome parameter. Changes in functional bladder capacity and intensity of pain and urgency have been chosen as secondary outcome parameters. Mood as well as physical and sexual activity were rated by 10 questions on a scale 0 to 6. The ratings were analyzed and the average for each patient in both groups Cystex® and placebo was determined as the quality of life index. For the primary outcome there was a statistically significant difference between the groups. Mean symptom score-sum decreased from 28.4 to 20.5 in the Cystex® group compared with 29.5 to 26.8 in the placebo group (p<0.05). For the secondary end points, pain and urgency intensity improved statistically significantly in the Cystex® group compared with the placebo group (p<0.05). The frequency and functional bladder capacity improved to greater degree in the Cystex® group. The differences were statistically significant for comparison of frequency (p<0.05) and not for functional bladder capacity (p>0.05). In our study, Cystex® enhanced quality of life over the placebo showing a statistically significant. This trial have shown that the efficacy and safety of therapy with Cystex® in the treatment of interstitial cystitis and is an alternative for patients suffering from this pathology. Therefore, it can be concluded that the composition of Cystex®, increased the quality of life in treated patients.
Keywords: Clinical trial; Interstitial cystitis; Painful bladder; Quality of life